Simpler optimized stellarators using permanent magnets. (1st August 2022) - Qian, T.; Zarnstorff, M.; Bishop, D.; Chamblis, A.; Dominguez, A.; Pagano, C.; Patch, D.; Zhu, C.
Abstract: A first-of-a-kind optimized stellarator for confining plasma has been designed and is being constructed with planar circular coils and permanent magnets composed of identical elements. The equilibrium is optimized to be quasi-axisymmetric for good particle confinement. The combination of permanent magnets and planar coils is significantly simpler to construct than fabricating three-dimensionally shaped coils, yet they are able to produce lower helical magnetic ripple than existing devices by two orders of magnitude in ϵ eff 3 / 2, a characteristic neoclassical transport metric.